Salat Jumat Perempuan di Gorontalo dalam Konstelasi Agama, Budaya, dan Ruang Publik: Analisis Filsafat Sosial - Rahmawati; Anwar, Ferlin; Yahiji, Kasim; Husain Hadi Pranata Wibawa, Nazar; Aminudin (Al-Ulum, 2025)
This research focuses on the controversy of women's Friday prayers in Gorontalo which arises from differences in ideological views, worship practices, and dynamics of socio-religious relations. The purpose of this research is to uncover the root of the conflict, explain the causative factors, and examine its social impact through the lens of social philosophy, especially related to power relations, the structure of religious authority, and the formation of religious public spaces. The research methods used are qualitative with theological-normative, sociological, religious, and social philosophy analysis approaches through observation, interviews, and documentation. The analysis was carried out inducively through reduction, verification, and data presentation by utilizing the concept of Stuart Hall reception. The results of the study show that there is a diversity of interpretations of QS. al-Jumu'ah verse 9 and hadith related to Friday obligations that result in dominant reception, negotiation, and opposition. These differences affect the configuration of religious power, strengthen gender boundaries in the worship space, and cause disharmony.